Examine the Moderating Role of Teacher’s Self-Efficacy in the Relationship Between the Job Satisfaction and Professional Learning Community in China - Li, Qiang-tian (Frontiers in Psychology, 2022)
Purpose: The study aimed in examining the impact of the professional learning community, and teachers’ self-efficacy on the job satisfaction of teachers. Additionally, the study has also examined the moderating role of teachers’ self-efficacy in the relationship between the PLC and job satisfaction. Method: The SEM-PLS is employed for the data analysis. The response rate of the study is 50%. The study is carried out on the primary teachers in China Results: Three research questions were developed in the current study. The questions were related to the job satisfaction level of PE teachers, which was far beyond the level of satisfaction. As a result, teachers of PE classes had low performance. It was found by the study that professional learning community, job satisfaction of teachers, and self-efficacy are linked with each other. However, the results are inconclusive because of the limitation of the sample Implications: The study has several implications among researchers, practitioners, and teachers. Significance: The study is among the few earlier studies on the issues related to Job Satisfaction and the professional learning community in China. Originality/Value: The study has highlighted an important issue related to the Job Satisfaction and professional learning community in China